Prediction of no‐reflow and major adverse cardiovascular events with a new scoring system in STEMI patients. (28th November 2017) - Bayramoğlu, Adil; Taşolar, Hakan; Kaya, Ahmet; Tanboğa, İbrahim Halil; Yaman, Mehmet; Bektaş, Osman; Günaydın, Zeki Yüksel; Oduncu, Vecih
Abstract : Background: No‐reflow is associated with a poor prognosis in STEMI patients. There are many factors and mechanisms that contribute to the development of no‐reflow, including age, reperfusion time, a high thrombus burden, Killip class, long stent use, ejection fraction ≤40, and a high Syntax score. In this study, we aimed to evaluate the parameters associated with no‐reflow prediction by creating a new scoring system. Methods: The study included 515 consecutive STEMI patients who underwent PCI; 632 STEMI patients who had undergone PCI in another center were included in the external validation of the scoring system. The correlations between 1‐year major adverse cardiac events and low/high risk score were assessed. Results: In this study, seven independent variables were used to build a risk score for predicting no‐reflow. The predictors of no‐reflow are age, EF ≤40, SS ≥22, stent length ≥20, thrombus grade ≥4, Killip class ≥3, and pain‐balloon time ≥4 h. In the derivation group, the optimal threshold score for predicting no‐reflow was >10, with a 75% sensitivity and 77.7% specificity (Area under the curve (AUC) = 0.809, 95%CI: 0.772‐0.842, P  < 0.001). In the validation group, AUC was 0.793 (95%CI: 0.760‐0.824, P  < 0.001). Conclusion: This new score, which can be calculated in STEMI patients before PCI and used to predict no‐reflow in STEMI patients, may help physicians to estimate the development of no‐reflow in the pre‐PCI period.